Selection of Official and Unofficial Lemon Raw Material Suppliers (Case Study of Tasikmalaya City Branch Mixue) - Muhammad Al-Gibran Ibnu Rismayadi; Vita Sarasi (Jurnal Impresi Indonesia, 2024)
Mixue is one of the most popular contemporary drink brands in Indonesia. One of the important raw materials for Mixue is lemon. In Indonesia, there are two types of lemon raw material suppliers, namely imported suppliers and local suppliers. This research aims to examine and compare the use of lemon raw materials from official suppliers of PT. Zhisheng Pacific Trading (MIXUE) imports raw materials from local suppliers in the context of use by Mixue retail stores operating in the food and beverage sector. This research uses mixed methods between qualitative methods and quantitative methods. Data collection techniques in this research were observation, interviews and questionnaires. Mixue is one of the most popular contemporary drink brands in Indonesia. Based on the results of this research, it can be concluded that local suppliers are superior to most of the factors considered than official suppliers. There is positive interest from experts involved in research regarding the use of lemon raw materials from local suppliers. From this research, recommendations and suggestions were obtained to consider updating policies related to regulations on the use of raw materials from third parties by considering all the advantages possessed by local suppliers in various factors. The results of this research state that local suppliers are superior in price and logistics efficiency. Official suppliers offer stable and reliable product quality.